STUDI SIFAT ELEKTROOPTIS PADA KACA AKUARIUM, KACA PREPARAT, DAN AKRILIK - Nila Kusuma, Anis; Firdausi, K. Sofjan; Setia Budi, Wahyu (BERKALA FISIKA, 2006)
The properties of electrooptics of transparency media such as aquarium glass, micro slides, and acrylic have been studied. To obtained the change of refractive index (Dn) of materials against external static electric field (E), the samples are placed in two parallel plates applied by potential different of Â 0 â€“ 104 V. The maximum external field reached by this experiment is in order 106 V/m. The change of refractive index as function of E is measured by Michelson interferometer equipment. First, our results show that the refractive index decreases as E increases for all samples. Second, Dn varies slightly square to E, which is still the dominant of linear electrooptic coefficient. The graphs both of acrylic and slides are rather smooth, which indicates that the crystal structures are more regular than aquarium glass. Key Words: electrooptics, refractive index, static electric field